A new 'golden age' for the antitubercular target InhA. Issue 3 (March 2017) - Rožman, Kaja; Sosič, Izidor; Fernandez, Raquel; Young, Robert J.; Mendoza, Alfonso; Gobec, Stanislav; Encinas, Lourdes
Highlights: Recent advances in development of InhA inhibitors are presented. We focus on inhibitors with a clear link to their in vivo activity. Collected crystallographic data to guide future efforts in drug design. A direct inhibitor of InhA could yield a promising clinical candidate. Abstract : The increasing prevalence of multidrug-resistant strains of Mycobacterium tuberculosis is the main contributing factor in unfavorable outcomes in the treatment of tuberculosis. Studies suggest that direct inhibitors of InhA, an enoyl-ACP-reductase, might yield promising clinical candidates that can be developed into new antitubercular drugs. In this review, we describe the application of different hit-identification strategies to InhA, which clearly illustrate the druggability of its active site through distinct binding mechanisms. We further characterize four classes of InhA inhibitors that show novel binding modes, and provide evidence of their successful target engagement as well as their in vivo activity. Abstract : This review provides insight into the most advanced InhA inhibitors, which show clear evidence of successful target engagement and represent excellent pointers for further drug optimization.